Restored perfusion and reduced inflammation in the infarcted heart after grafting stem cells with a hyaluronan‐based scaffold. Issue 4 (11th March 2013) - Muscari, Claudio; Bonafè, Francesca; Martin‐Suarez, Sofia; Valgimigli, Simond; Valente, Sabrina; Fiumana, Emanuela; Fiorelli, Federico; Rubini, Giuseppe; Guarnieri, Carlo; Caldarera, Claudio Marcello; Capitani, Ombretta; Arpesella, Giorgio; et al.
Abstract The aim of this study is to investigate the blood perfusion and the inflammatory response of the myocardial infarct area after transplanting a hyaluronan‐based scaffold (HYAFF®11) with bone marrow mesenchymal stem cells (MSCs). Nine‐week‐old female pigs were subjected to a permanent left anterior descending coronary artery ligation for 4 weeks. According to the kind of the graft, the swine subjected to myocardial infarction were divided into the HYAFF®11, MSCs, HYAFF®11/MSCs and untreated groups. The animals were killed 8 weeks after coronary ligation. Scar perfusion, evaluated by Contrast Enhanced Ultrasound echography, was doubled in the HYAFF®11/MSCs group and was comparable with the perfusion of the healthy, non‐infarcted hearts. The inflammation score of the MSCs and HYAFF®11/MSCs groups was near null, revealing the role of the grafted MSCs in attenuating the cell infiltration, but not the foreign reaction strictly localized around the fibres of the scaffold. Apart from the inflammatory response, the native tissue positively interacted with the HYAFF®11/MSCs construct modifying the extracellular matrix with a reduced presence of collagene and increased amount of proteoglycans. The border‐zone cardiomyocytes also reacted favourably to the graft as a lower degree of cellular damage was found. This study demonstrates that the transplantation in the myocardial infarct area of autologous MSCs supported by a hyaluronan‐based scaffold restores blood perfusion and almost completely abolishes the inflammatory process following an infarction. These beneficial effects are superior to those obtained after grafting only the scaffold or MSCs, suggesting that a synergic action was achieved using the cell‐integrated polymer construct.